ANALYSIS OF THE EFFECT OF ABSORBTIVE CAPACITY ON THE PERFORMANCE OF S1 MANAGEMENT STUDY PROGRAMS IN KOPERTIS IV WEST JAVA-BANTEN - Maryani Maryani (Dinasti Publisher, 2020)
The capacity to absorb knowledge is the ability of organization to gather external information which is then used for organizational development and innovation. The development of the education world, rapid competition and intense competition among study programs, especially management study programs, require the determination of innovation strategies that have competitive advantages. The success of an organization in facing competition depends on how the organization optimizes the capacity of absorbing knowledge that has an impact on the performance of the study program. This research was conducted on the S1 Management Study Programs at Kopertis 4 West Java. The method used in this research is descriptive and verification method. It also used Structural Equation Modeling (SEM) analysis technique. The ability to absorb knowledge is shaped by 4 dimensions, namely the ability to acquire knowledge, the ability to assimilate knowledge, the ability to transform knowledge, and the ability to exploit knowledge. The results showed that the ability to absorb knowledge has a high contribution to the performance of study programs. The dimension of the ability to transform knowledge is the largest dimension contributing to the ability to absorb knowledge with a loading factor of 0.811 with an r2 value of 65.7%. The ability to absorb knowledge significantly influences the performance of study programs.